Are the spiral arms in the MWC 758 protoplanetary disc driven by a companion inside the cavity?. Issue 1 (18th August 2020) - Calcino, Josh; Christiaens, Valentin; Price, Daniel J; Pinte, Christophe; Davis, Tamara M; van der Marel, Nienke; Cuello, Nicolás
ABSTRACT: Spiral arms in protoplanetary discs are thought to be linked to the presence of companions. We test the hypothesis that the double spiral arm morphology observed in the transition disc MWC 758 can be generated by an ≈10 M Jup companion on an eccentric orbit internal to the spiral arms. Previous studies on MWC 758 have assumed an external companion. We compare simulated observations from three-dimensional hydrodynamics simulations of disc–companion interaction to scattered light, infrared and CO molecular line observations, taking into account observational biases. The inner companion hypothesis is found to explain the double spiral arms, as well as several additional features seen in MWC 758 – the arc in the north-west, substructures inside the spiral arms, the cavity in CO isotopologues, and the twist in the kinematics. Testable predictions include detection of fainter spiral structure, detection of a point source south-southeast of the primary, and proper motion of the spiral arms.